Engineering and commercialization of human-device interfaces, from bone to brain. (July 2016) - Knothe Tate, Melissa L.; Detamore, Michael; Capadona, Jeffrey R.; Woolley, Andrew; Knothe, Ulf
Abstract: Cutting edge developments in engineering of tissues, implants and devices allow for guidance and control of specific physiological structure-function relationships. Yet the engineering of functionally appropriate human-device interfaces represents an intractable challenge in the field. This leading opinion review outlines a set of current approaches as well as hurdles to design of interfaces that modulate transfer of information, i.a. forces, electrical potentials, chemical gradients and haptotactic paths, between endogenous and engineered body parts or tissues. The compendium is designed to bridge across currently separated disciplines by highlighting specific commonalities between seemingly disparate systems, e.g. musculoskeletal and nervous systems. We focus on specific examples from our own laboratories, demonstrating that the seemingly disparate musculoskeletal and nervous systems share common paradigms which can be harnessed to inspire innovative interface design solutions. Functional barrier interfaces that control molecular and biophysical traffic between tissue compartments of joints are addressed in an example of the knee. Furthermore, we describe the engineering of gradients for interfaces between endogenous and engineered tissues as well as between electrodes that physically and electrochemically couple the nervous and musculoskeletal systems. Finally, to promote translation of newly developed technologies into products, protocols, and treatments that benefit the patients who need them most, regulatory and technical challenges and opportunities are addressed on hand from an example of an implant cum delivery device that can be used to heal soft and hard tissues, from brain to bone.